1984
DOI: 10.1111/j.1423-0410.1984.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurization of C1 Inactivator in the Presence of Citrate Salts1,2

Abstract: Conditions have been determined under which the C1 inactivator (C1-INA) can be pasteurized to reduce the risk of transfusion hepatitis associated with its use for replacement therapy in patients with genetic or acquired deficiencies. Recovery of 90% of the biological and immunological activity of a C1-INA concentrate was achieved following heat treatment for 10 h at 60 degrees C in the presence of 3 M potassium citrate. Crossed immunoelectrophoresis in heparinized agarose was used to demonstrate the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, for C1-inhibitor 6, [31][32][33]. Although of use for clinical concentrates, for research purposes it is not always desirable to have certain other criteria need to be met.…”
Section: But Was Probably a Dimer Therefore This Methods Is Amentioning
confidence: 99%
“…However, for C1-inhibitor 6, [31][32][33]. Although of use for clinical concentrates, for research purposes it is not always desirable to have certain other criteria need to be met.…”
Section: But Was Probably a Dimer Therefore This Methods Is Amentioning
confidence: 99%
“…Starting from the eighties, policies for donors' selection and the introduction of specific manufacturing processes, drastically reduced the risk of viral infection from blood products. Since 1985, different plasmaderived C1-INH (pdC1-INH) preparations were registered in Europe for acute treatment of HAE attacks, and no further evidence of infection related to these preparations has ever been reported [6][7][8][9]. Despite the extended use of pdC1-INH, the first registrative study was published in 2009 [7].…”
Section: Plasma-derived C1-inhmentioning
confidence: 99%
“…Since 1985, different plasmaderived C1-INH (pdC1-INH) preparations were registered in Europe for acute treatment of HAE attacks, and no further evidence of infection related to these preparations has ever been reported [6][7][8][9]. Despite the extended use of pdC1-INH, the first registrative study was published in 2009 [7]. It was a randomized, placebo-controlled, double-blind study that compared the efficacy of pasteurized C1 esterase inhibitor concentrate (Berinert®, CSL Behring) with placebo in the treatment of single, acute abdominal or facial attacks in patients with HAE.…”
Section: Plasma-derived C1-inhmentioning
confidence: 99%
“…Crossed immunoelectrophoresis (CIEP) was carried out as previously described [22], with antiserum to CI-INA (Behring Diagnostics) incorporated in the gel for the second dimension.…”
Section: Large-scale Preparation Of Intermediate-purity Ci-ina Concenmentioning
confidence: 99%
“…However, in later studies [20, 211, the presence of sucrose was found to significantly reduce the virus inactivation rate during heat treatment. We reported that Cl-INA could withstand pasteurization treatment in the presence of 3 M potassium citrate [22], but a subsequent test using chimpanzees revealed that under these conditions, the HBV was stabilized as well [23].…”
mentioning
confidence: 99%